FREEZE DRYING OF FISHERY PRODUCTS:PART IV -BIOCHEMICAL CHANGES OCCURRING IN PRAWN MUSCLE DURING FREEZING,FREEZE DRYING AND PROLONGED STORAGE OF THE FREEZE DRIED PRODUCT. - GOVINDAN, T K (Fishery Technology, 2017)
The changes occurring in water and sa1t extractable proteinand non-protein fractions in prawn muscle of different speciesduring freezing, freeze drying and subsequent prolonged storagehave been studied. There is no denaturation of water extractableproteins, whereas salt extractable proteins wen renderedinsoluble to the extent of 21% due to freeze drying. Thefreeze dried products remained in good edible condition for32 months of storage up to which sto1age characteristics werefollowed.